The Net, Cybermoney, and Credit Risks : New Technologiy, and Payment System Risks - Minehan, Cathy E. (World Bank, Washington, DC, 2012)
Smart cards, electronic checks, and electronic money alternatives combined with broadly available communications facilities such as the Internet are rapidly increasing the choices for retail payments. They are also increasing the risks. The author reviews the lessons for risk management from the earlier technological changes in the wholesale system.